2016
DOI: 10.1590/bjpt-rbf.2014.0174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a progressive resistance exercise program with high-speed component on the physical function of older women with sarcopenic obesity: a randomized controlled trial

Abstract: BackgroundSarcopenic obesity is associated with disability in older people, especially in women. Resistance exercises are recommended for this population, but their efficacy is not clear.ObjectiveTo evaluate the effects of a progressive resistance exercise program with high-speed component on the physical function of older women with sarcopenic obesity.MethodTwenty-eight women 65 to 80 years old, with a body mass index ≥30kg/m2 and handgrip strength ≤21kg were randomly allocated to two groups. The experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 28 publications
3
100
0
Order By: Relevance
“…We included several behavior change methods that may have contributed to the marked increase in QoL, such as self‐regulation, peer support, and goal setting. Indeed, recent resistance training studies reporting an increase in QoL have employed behavior change techniques such as goal setting, whereas those showing no change in QoL did not report the use of behavior change methods . Interestingly, the difference in EQ‐VAS favored the ST group at 3 months ( g s = 0.50, [−0.14, to 1.15]), although this difference was not evident at 6 months ( g s = 0.35 [−0.29 to 0.99]).…”
Section: Discussionmentioning
confidence: 99%
“…We included several behavior change methods that may have contributed to the marked increase in QoL, such as self‐regulation, peer support, and goal setting. Indeed, recent resistance training studies reporting an increase in QoL have employed behavior change techniques such as goal setting, whereas those showing no change in QoL did not report the use of behavior change methods . Interestingly, the difference in EQ‐VAS favored the ST group at 3 months ( g s = 0.50, [−0.14, to 1.15]), although this difference was not evident at 6 months ( g s = 0.35 [−0.29 to 0.99]).…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant and rising public health concerns, SO is a modifiable condition and can be treated with effective therapy. In this sense, it has been argued that exercise training interventions and, in particular, resistance training (RT) could ameliorate outcomes related to SO by promoting beneficial changes in muscle strength 11 , 12 and adiposity indices. 13 However, a more careful analysis of intervention studies in elderly individuals with SO has shown conflicting results with respect to improvements in physical function.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research indicated that measuring the process of change, using the transtheoretical model, of physical activity and exercise in overweight and obese adults supports the validity of the factorial structure for weight management10 ) . Contrary to positive research findings, one study found that a progressive resistance exercise program with high-speed components was not effective in improving the physical function of older women with sarcopenic obesity11 ) . The multicomponent intervention including behavioral self-monitoring, computer-based training, and motivational interviewing for truck drivers was supported in the United States12 ) .…”
Section: Discussionmentioning
confidence: 87%